ANALYSIS OF APPROACHES TO EVALUATION OF REGION’S INVESTMENT ATTRACTIVENESS - ZAVHORODNIA, TETIANA; TKACHENKO, IVAN; BEDNARSKYI, KOSTIANTYN (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Sustainable regional development is determined by continuous investment and innovation stimulation of economic processes. The regional level of state investment policy involves the use of a system of measures aimed at attracting and efficient use of investment resources coming from economic entities of all forms of ownership to ensure stable socially oriented development of the region. The lack of a regional investment and innovation model of regional development does not allow to develop and implement a set of measures aimed at counteracting modern challenges and disturbances. The article examines issues related to assessing the investment attractiveness of regions. The influence of investment and innovation processes on the sustainable development of the regions is studied. The conclusion is made about the role of investment attractiveness of regions to ensure their financial self-sufficiency. Modern approaches of scientists to the interpretation of the content of the category of investment attractiveness are analyzed. It is established that this is a complex, multifaceted economic category that characterizes the regional space’s complexity in terms of the existing investment climate, the state, and the level of development of the relevant investment infrastructure. The article analyzes the current approaches to assessing investment attractiveness. It is established that such a task is solved within the framework of three main scientific and methodological approaches: statistical, rating, and expert. Within the framework of each approach, their features and directions of realization for the decision of the set tasks are considered. Based on the analysis, a conclusion was formed on the integrated application of methods for assessing the region’s investment attractiveness for innovation and investment decisions.